Predictors of Relapse in Children with Steroid-Sensitive Nephrotic Syndrome - Shafiullah, Mohammad; Muinuddin, Golam; Rahman, Habibur; Ahmed, Farid; Islam, Md Shafiqul; Karim, AKM Rezaul (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17384 Ibrahim Cardiac Med J 2012; 2(1): 21-26